Hypothermia combined with neuroprotective adjuvants shortens the duration of hospitalization in infants with hypoxic ischemic encephalopathy: Meta-analysis - Ovcjak, Andrea; Pontello, Riley; Miller, Steve P.; Sun, Hong-Shuo; Feng, Zhong-Ping (Frontiers in Pharmacology, 2023)
Objective: Therapeutic hypothermia (TH) is the current standard of care for neonatal hypoxic–ischemic encephalopathy (HIE), yet morbidity and mortality remain significant. Adjuvant neuroprotective agents have been suggested to augment hypothermic-mediated neuroprotection. This analysis aims to identify the classes of drugs that have been used in combination with hypothermia in the treatment of neonatal HIE and determine whether combination therapy is more efficacious than TH alone. Methods: A systematic search of PubMed, Embase and Medline from conception through October 2021 was conducted. Randomized- and quasi-randomized controlled trials, observational studies and retrospective studies evaluating HIE infants treated with combination therapy versus TH alone were selected. Primary reviewers extracted information on mortality, neurodevelopmental impairment and length of hospitalization for meta-analyses. Effect sizes were pooled using a random-effects model and measured as odds ratio (OR) or mean difference (MD) where applicable, and 95% confidence intervals (CI) were calculated. Risk of bias was assessed using the tool from the Cochrane Handbook for Systematic Reviews of Interventions Results: The search strategy collected 519 studies, 16 of which met analysis inclusion criteria. HIE infants totaled 1292 from included studies, 642 infants received some form of combination therapy, while 650 infants received TH alone. GABA receptor agonists, NMDA receptor antagonists, neurogenic and angiogenic agents, stem cells, glucocorticoids and antioxidants were identified as candidate adjuvants to TH. Length of hospitalization was significantly reduced in infants treated with combination therapy (MD -4.81, 95% CI [-8.42. to -1.19], P = 0.009) compared to those treated with TH alone, while risk of mortality and neurodevelopmental impairment did not differ. Conclusion: Compared to the current standard of care, administration of neuroprotective adjuvants with TH reduced the duration of hospitalization but did not impact the risk of mortality or neurodevelopmental impairment in HIE infants, likely due to the limits by a moderate risk of bias among included studies and small sample sizes. This analysis highlights the needs for preclinical trials to conduct drug development studies and identify relevant molecular targets that may offer additive or synergistic neuroprotection to TH, and for clinical trials to determine the dose and timing of administration of adjuvant neuroprotectants.